Perceptions and experiences related to use of breastmilk from another mother in central Nepal: a qualitative study - Akina Shrestha; Natalie Gulrajani; Amy Sarah Ginsburg; Victoria Laleau; Soujanya Gade; Valerie Flaherman; Mahesh C. Puri; Srijana Dongol (International Breastfeeding Journal)
Abstract Background When maternal breastmilk is unavailable in sufficient quantity for infant needs, the World Health Organization (WHO) recommends the use of donor breastmilk if safe, affordable, and available. However, in Nepal and most other low- and middle-income countries (LMICs), there are significant barriers to accessing safe and affordable donor breastmilk, including a paucity of milk banks. An in-depth understanding of perceptions and experiences in Nepal related to use of donor breastmilk could inform the development of interventions to address identified barriers. Methods From December 2019 to January 2020, we conducted a qualitative study, including focus group discussions (FGDs) with parents and community health workers (CHW), and key informant interviews (KIIs) with public health stakeholders in Dhulikhel municipality, Kavrepalanchowk district in Nepal. In total, 44 individuals participated in five FGDs, including two with mothers, one with fathers, and two with CHW. Nine KIIs were conducted with stakeholders. Thematic analyses of translated transcripts were undertaken to explore perceptions and experiences of participants related to use of human donor breastmilk. Results Participants in this study reported that informal breastmilk sharing between relatives and neighbors is common when a mothers’ breastmilk is unavailable or insufficient and such sharing can occur via direct breastfeeding or milk expression. Numerous potential benefits with breastmilk sharing were described, including overcoming initial difficulties with milk supply in the postpartum period, convenience when mothers are unavailable, and reduced risk of infant infection and gastrointestinal distress. Hesitancies to breastmilk sharing included the risk of disease transmission from donor to infant and the possibility of decreased bonding between mother and infant. Some participants stated that animal milk is preferable to breastmilk sharing when mothers own milk is not available. Conclusion Participants were aware of the potential benefits of donor breastmilk but identified numerous barriers to widespread adoption, including concerns about infectious diseases and mother-infant bonding, and preference for animal milks over another mother’s milk. Addressing these concerns may help increase the acceptance and practice of donating and using donor breastmilk among mothers in Nepal.